Suppressing Atrocity Speech on Social Media. (2019) - Irving, Emma
Abstract : In its August 2018 report on violence against Rohingya and other minorities in Myanmar, the Fact Finding Mission of the Office of the High Commissioner for Human Rights noted that "the role of social media [was] significant" in fueling the atrocities. Over the course of more than four hundred pages, the report documented how Facebook was used to spread misinformation, hate speech, and incitement to violence in the lead-up to and during the violence in Myanmar. Concluding that there were reasonable grounds to believe that genocide was perpetrated against the Rohingya, the report indicated that "the Mission has no doubt that the prevalence of hate speech, " both offline and online, "contributed to increased tension and a climate in which individuals and groups may become more receptive to incitement." The experience in Myanmar demonstrates the increasing role that social media plays in the commission of atrocities, prompting suggestions that social media companies should operate according to a human rights framework.